Rare bird documentation form for Peregrine Falcon along the Skunk River in Ames, 1983 - Martsching, Paulet al (1983)
Rare bird documentation form for a Peregrine Falcon along the Skunk River in Ames in Story County, IA on November 6, 1983. Epson - sheet feed